Independent allopatric polyploidizations shaped the geographical structure and initial stage of reproductive isolation in an allotetraploid fern, Lepisorus nigripes (Polypodiaceae). - Tao Fujiwara; Yasuyuki Watano (PLoS ONE, 2020)
Although polyploidy is pervasive and its evolutionary significance has been recognized, it remains unclear how newly formed polyploid species become established. In particular, the impact of multiple origins on genetic differentiation among populations of a polyploid species and whether lineages of independent origins have different evolutionary potentials remain open questions. We used population genetic and phylogenetic approaches to identify genetic differentiation between lineages with independent origins within an allotetraploid fern, Lepisorus nigripes. A total of 352 individuals from 51 populations were collected throughout the distribution range. To examine the genetic structure, multilocus genotyping, Bayesian population structure analysis, and neighbor-net analysis were carried out using single-copy nuclear genes. Phylogenetic trees were constructed to detect recurrent polyploid origins. Proportions of abortive spores were analysed as the measure of postzygotic reproductive isolation. Two genetically distinct lineages, the East-type and the West-type, were distributed mainly in the eastern and western parts, respectively, of the Japanese archipelago. Phylogenetic analyses indicated independent origins of these types and detected additional independent origins within each type. We also revealed limited genetic recombination between both types, even in their sympatric regions. F1 hybrids between the East- and West-types showed a reduction in fertility. It is likely that the East- and West-types formed independently in the eastern and western parts of Japan, respectively. The limited genetic recombination and reduced fertility of hybrids suggest that the two types are at an incipient stage of speciation. Two polyploid lineages with independent geographic origins could develop reproductive isolation barrier(s).